The Current Consideration, Approach, and Management in Postcesarean Delivery Pain Control: A Narrative Review - L. Sangkum; T. Thamjamrassri; V. Arnuntasupakul; T. Chalacheewa (Anesthesiology Research and Practice)
Optimal postoperative analgesia has a significant impact on patient recovery and outcomes after cesarean delivery. Multimodal analgesia is the core principle for cesarean delivery and pain management. For a standard analgesic regimen, the use of long-acting neuraxial opioids (e.g., morphine) and adjunct drugs, such as scheduled acetaminophen and nonsteroidal anti-inflammatory drugs, is recommended unless contraindicated. Oral or intravenous opioids should be reserved for breakthrough pain. In addition to the aforementioned use of multimodal analgesia, preoperative evaluation is critical to individualize the analgesic regimen according to the patient requirements. Risk factors for severe postoperative pain or analgesia-related adverse effects will require modifications to the standard analgesic regimen (e.g., the use of ketamine, gabapentinoids, or regional anesthetic techniques). Further investigation is required to determine analgesic drugs or dose alterations based on preoperative predictions for patients at risk of severe pain. Outcomes beyond pain and analgesic use, such as functional recovery, should be determined to evaluate analgesic treatment protocols.